Jésuites et Cisterciens dans la France des premiers Bourbons : un aspect de l’antijésuitisme ? - Bertrand Marceau (Chrétiens et Sociétés, 2015)
Whereas the historiography showed the diversity and plasticity of the anti-Jesuitism, the Cistercian monks added a figure of anti-Jesuitism to the previous ones in the second half of the sixteenth century. This intra-ecclesial anti-Jesuitism is based on a clear opposition between traditional monasticism and the secular congregation. It grows particularly with the policy of the Jesuits in the kingdom of France in the years 1600-1610. This raises the problem of relations between this two actors of the Catholic Reform, both their rivalry (especially the Cistercian anti-Jesuit defense policy) and their complementarity (the ambivalence of their relationship can not be reduced to an opposition). Indeed, the widely activist and defensive anti-Jesuitism of the Cistercian monks is juxtaposed with attitudes of conciliation and even favor, attitudes that invite to think about the different ways in which men of the same generation and the same faith invested the political and religious crisis of the late sixteenth century and one of the remedies proposed, the Societas Jesu. In this sense, beyond contextual and strong opposition, emerges a form of ecclesiological complementarity between this different religious.